Strain Modulation of Selectively and/or Globally Grown Ge Layers - Du, Yong (Nanomaterials (Basel), 2021)
This article presents a novel method to grow a high-quality compressive-strain Ge epilayer on Si using the selective epitaxial growth (SEG) applying the RPCVD technique. The procedures are composed of a global growth of Ge layer on Si followed by a planarization using CMP as initial process steps. The growth parameters of the Ge layer were carefully optimized and after cycle-annealing treatments, the threading dislocation density (TDD) was reduced to 3 × 10(7) cm(−2). As a result of this process, a tensile strain of 0.25% was induced, whereas the RMS value was as low as 0.81 nm. Later, these substrates were covered by an oxide layer and patterned to create trenches for selective epitaxy growth (SEG) of the Ge layer. In these structures, a type of compressive strain was formed in the SEG Ge top layer. The strain amount was −0.34%; meanwhile, the TDD and RMS surface roughness were 2 × 10(6) cm(−2) and 0.68 nm, respectively. HRXRD and TEM results also verified the existence of compressive strain in selectively grown Ge layer. In contrast to the tensile strained Ge layer (globally grown), enhanced PL intensity by a factor of more than 2 is partially due to the improved material quality. The significantly high PL intensity is attributed to the improved crystalline quality of the selectively grown Ge layer. The change in direct bandgap energy of PL was observed, owing to the compressive strain introduced. Hall measurement shows that a selectively grown Ge layer possesses room temperature hole mobility up to 375 cm(2)/Vs, which is approximately 3 times larger than that of the Ge (132 cm(2)/Vs). Our work offers fundamental guidance for the growth of high-quality and compressive strain Ge epilayer on Si for future Ge-based optoelectronics integration applications.